Kepemimpinan Demokratis Kepala Madrasah Ibtidaiyah Swasta (MIS) MIS Nurul Muslimin Sungai Raya Kuburaya - Hamidah Hamidah (The Magister of Islamic Education Study Program of Postgraduate IAIN Pontianak, 2022)
The purpose of this study is to find out and explain about democratic leadership that is appropriate to be implemented in the Nurul Muslimin Private Madrasah Ibidaiyah (MIS). The urgent problem at MIS Nurul Muslimin is that the leadership has not demonstrated a democratic one yet. This research is a qualitative descriptive research, namely data analysis that emphasizes meaning, reasoning, defining certain situations (in certain contexts) and describing what is about the behavior of the object under study. Data collection tools used are interviews, observation, and documentation. While the results of the research can be concluded that democratic leadership is needed and important to overcome and realize quality MIS Nurul Muslimin Sungai Raya in the future. Democratic leadership that exists at MIS Nurul Muslimin, such as receiving opinions, suggestions and criticism from subordinates, prioritizing cooperation and teamwork, coordinating with subordinates, providing stimulation to subordinates to be productive, involving subordinates in solving problems, providing information about duties and responsibilities subordinate. ABSTRAK Tujuan penelitian ini untuk mengetahui dan menjelaskan tentang kepemimpinan demokratis yang tepat untuk diterapkan di Madrasah Ibidaiyah Swasta(MIS) Nurul Muslimin. Masalah yang ada di MIS Nurul Muslimin saat ini kepemimpinan belum menunjukkan yang demokratis. Penelitian ini termasuk penelitian deskriptif kualitatif, yaitu analisis data yang menekankan pada makna, penalaran, pendefinisian situasi tertentu (dalam konteks tertentu) dan mendeskripsikan apa adanya tentang perilaku objek yang diteliti. Alat pengumpulan data yang digunakan adalah wawancara, observasi, dan dokumentasi. Sedangkan hasil penelituan dapat disimpulkan bahwa kepemimpinan demokratis sangat dibutuhkan dan penting untuk mengatasi serta mewujudkan MIS Nurul Muslimin Sungai Raya bermutu di masa depan. Kepemimpinan yang demokratis yang ada di MIS Nurul Muslimin, seperti menerima pendapat, saran dan kritik dari bawahan, mengutamakan kerjasama dan kerjasama tim, berkoordinasi dengan bawahan, memberikan rangsangan kepada bawahan untuk produktif, melibatkan bawahan dalam memecahkan masalah, memberikan informasi tentang tugas dan tanggung jawab bawahan. Kata kunci: kepemimpinan, demokratis